Respuesta :
[tex]\\ \rm\longmapsto 2^{4x+4}=64^{x+2}[/tex]
[tex]\\ \rm\longmapsto 2^{4x+4}=(2^6)^{x+2}[/tex]
[tex]\\ \rm\longmapsto 2^{4x+4}=2^{6(x+2)}[/tex]
[tex]\\ \rm\longmapsto 4x+4=6(x+2)[/tex]
[tex]\\ \rm\longmapsto 4x+4=6x+12[/tex]
[tex]\\ \rm\longmapsto 4-12=6x-4x[/tex]
[tex]\\ \rm\longmapsto -8=2x[/tex]
[tex]\\ \rm\longmapsto x=\dfrac{-8}{2}[/tex]
[tex]\\ \rm\longmapsto x=-4[/tex]
Answer:
x = 1
Step-by-step explanation:
[tex] {2}^{4x + 14} = {64}^{x + 2} [/tex]
➡️ [tex] {2}^{4x + 14} = ( {2}^{6} {)}^{x + 2} [/tex]
➡️ [tex] {2}^{4x + 14} = {2}^{6x + 12} [/tex]
➡️ [tex]4x + 14 = 6x + 12[/tex]
➡️ [tex]14 - 12 = 6x - 4x[/tex]
➡️ [tex]2x = 2[/tex]
➡️ [tex]x = 1[/tex]